Measuring Self-Control Problems - Ameriks, John; Caplin, Andrew; Leahy, John; Tyler, Tom (The American economic review, 2007)
We develop a survey instrument to measure self-control problems in a sample of highly educated adults. This measure relates in the manner that theory predicts to liquid wealth accumulation and personality measures. Yet while self-control problems are typically seen as resulting in overconsumption and low wealth, we identify a significant group who underconsume and thereby accumulate high levels of wealth. In addition, self-control problems are smaller in scale for older than for younger respondents. Those who put money aside in retirement accounts may be delaying access to a point at which self-control problems are no longer important. (JEL D12, D14)